THE INFLUENCE OF LEADERSHIP STYLE, WORK ENVIRONMENT, AND COMPETENCE ON EMPLOYEE PERFORMANCE AT THE CULTURE AND TOURISM OFFICE OF SOUTH SULAWESI PROVINCE: University of Muhammadiyah Makassar - Rusli, Rusli; Akhmad, Akhmad; Rizal, Samsul; Mustari, Nuryanti (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2025)
This study aims to find out and analyze the influence of leadership style, work environment, and competence on employee performance at the South Sulawesi Provincial Culture and Tourism Office. The method used in this study is a quantitative research method with the category of explanatory research, which is research that aims to analyze the relationship between independent (influencing) and dependent variables on a sample of 125 respondents using a questionnaire as a source of data collection. The analysis used was multiple linear regression analysis using the IBM SPSS Statistic 25 application. The results of the study showed that leadership style had a positive and significant effect on employee performance with P = 0.000 < 0.05 and a coefficient value of 7.068. Meanwhile, the work environment showed that there was a positive but not significant influence on employee performance with P = 0.872 > 0.05 and a coefficient value of 0.161. Likewise, competence shows that there is a positive and significant influence on employee performance at the South Sulawesi Provincial Culture and Tourism Office with P = 0.000 < 0.05 and a coefficient value of 16.087. With this, it is concluded that leadership style, work environment, and competence have an influence on employee performance at the South Sulawesi Provincial Culture and Tourism Office.